2022
DOI: 10.3389/fendo.2022.890057
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Prediction for the Risk of Diabetic Foot in Patients With Type 2 Diabetes Mellitus

Abstract: AimsTo develop and validate a nomogram prediction model for the risk of diabetic foot in patients with type 2 diabetes mellitus (T2DM) and evaluate its clinical application value.MethodsWe retrospectively collected clinical data from 1,950 patients with T2DM from the Second Affiliated Hospital of Xi’an Jiaotong University between January 2012 and June 2021. The patients were divided into training cohort and validation cohort according to the random number table method at a ratio of 7:3. The independent risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…HbA 1c is an independent risk factor for the development of DFUs. [25] Similarly, in a metaanalysis published by Tang et al, HbA 1c level was shown to be one of the factors predicting the development of DFU. [26] The results of the present study revealed a significant correlation between the high HbA 1c values on presentation with the severity of diabetic foot, the surgical procedures applied, and the level of tissue loss present in the patients with diabetic foot.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HbA 1c is an independent risk factor for the development of DFUs. [25] Similarly, in a metaanalysis published by Tang et al, HbA 1c level was shown to be one of the factors predicting the development of DFU. [26] The results of the present study revealed a significant correlation between the high HbA 1c values on presentation with the severity of diabetic foot, the surgical procedures applied, and the level of tissue loss present in the patients with diabetic foot.…”
Section: Discussionmentioning
confidence: 88%
“…HbA 1c is an independent risk factor for the development of DFUs. [ 25 ] Similarly, in a meta-analysis published by Tang et al, HbA 1c level was shown to be one of the factors predicting the development of DFU. [ 26 ]…”
Section: Discussionmentioning
confidence: 96%
“…For diabetic patients, leg ulceration is the main cause of lower limb amputation. DM is also responsible for the majority of non-traumatic amputations, 85% of which are predisposed by foot ulceration [78][79][80]. The occurrence of ulcers in diabetic patients is accompanied by a high rate of morbidity and mortality, and also represents an economic and social burden through its implications for functional status and quality of life [81].…”
Section: Diabetic Foot Syndromementioning
confidence: 99%
“…At present, the gold standard for the diagnosis of diabetic peripheral neuropathy is nerve conduction studies; however, these are labor-intensive, time-consuming, expensive, and impractical ( 29 ). Diagnosing diabetic foot requires examination of both lower limb arteries and foot and ankle orthopedic examination by color Doppler ultrasound, which is time-consuming and costly ( 30 ). Therefore, it is difficult to obtain comprehensive prediction indicators.…”
Section: Introductionmentioning
confidence: 99%